Metal nanoparticles in microbiology - Rai, Mahendra; Duran, Nelson (Springer, 2011)
Following an introduction to biogenic metal nanoparticles, this book presents how they can be biosynthesized using bacteria, fungi and yeast, as well as their potential applications in biomedicine. It is shown that the synthesis of nanoparticles using microbes is eco-friendly and results in reproducible metal nanoparticles of well-defined sizes, shapes and structures. This biotechnological approach based on the process of biomineralization exploits the effectiveness and flexibility of biological systems. Chapters include practical protocols for microbial synthesis of nanoparticles and microbial screening methods for isolating a specific nanoparticle producer as well as reviews on process optimization, industrial scale production, biomolecule-nanoparticle interactions, magnetosomes, silver nanoparticles and their numerous applications in medicine, and the application of gold nanoparticles in developing sensitive biosensors.